1959
DOI: 10.1083/jcb.6.2.277
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Rhodospirillum rubrum

Abstract: Cells from serial cultures of R. rubrum, grown anaerobically in the light, were harvested at intervals from ~/~ to 15 days and sectioned for electron microscopy by conventional methods.Cells of this species possess a multilayered outer envelope, and the external cell surface is differentiated into ridges extending parallel or obliquely to the long axis of the cell.Cells from very young cultures resemble non-photosynthetic bacteria and contain only a granular cytoplasm, scattered high-density particles, and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

1962
1962
1993
1993

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 18 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…Electron micrographs of light grown Rhodopseudomonas spheroides or Rhodospirillum rubrum show the cytoplasm to contain round, electron transparent structures which increase in number as the pigment content of the cell increases. These structures are not seen in micrographs of aerobically grown cells (Hickman & Frenkel, 1959;Flexer, Sistrom & Chapman, 1960). Newton (1960) has shown that pigmented cells of R. rubrum contain antigens which are not present in aerobically grown cells.…”
Section: Introductionmentioning
confidence: 99%
“…Electron micrographs of light grown Rhodopseudomonas spheroides or Rhodospirillum rubrum show the cytoplasm to contain round, electron transparent structures which increase in number as the pigment content of the cell increases. These structures are not seen in micrographs of aerobically grown cells (Hickman & Frenkel, 1959;Flexer, Sistrom & Chapman, 1960). Newton (1960) has shown that pigmented cells of R. rubrum contain antigens which are not present in aerobically grown cells.…”
Section: Introductionmentioning
confidence: 99%
“…The circular cytoplasmic bodies shown here have been observed previously (7), and in some areas are connected to one another by lamellae which are continuous with the cytoplasmic membrane (arrow). OsO4 fixation.…”
Section: Figure 16mentioning
confidence: 48%
“…As previously indicated (7) the ages of these cultures should be considered approximate and are used only to establish the relative ages of the cultures . Fig .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations